Creating and testing carbon interfaces - Integrating oligomeric phthalocyanines onto single walled carbon nanotubes - Strauß, Volker; Gallego, Almudena; De La Torre, Gema; Chamberlain, Thomas W.; Khlobystov, Andrei N.; Torres, Tomas; Guldi, Dirk Michael (Faraday Discussions, 2014)
Two oligomers, that is, para-phenylenevinylene with either pendant Pd(II)Pc or Zn(II)Pc units, have been synthesized and their interactions with SWCNTs and peapods - C60@SWCNT - have been probed by complementary spectroscopy and microscopy. Spectroscopy assisted mainly in shedding light onto electronic interactions in the ground and excited state, while microscopy enabled insights into the degree of individualizing SWCNTs/C60@SWCNTs and their stabilization.
CRIS-Team Scopus Importer:2023-03-07